KENALI DAN HINDARI PENTINGNYA KESADARAN REMAJA TERHADAP PRAKTIK CHILD GROOMING MELALUI PROGRAM PENYULUHAN HUKUM: SOSIALISASI DI MA DARUL IRFAN KOTA SERANG - Muhammad Farrel Brastama; Fifi Rahmawati Ningrum; Samsul Maarip; Luthfi Hammid Jamaludin; Tabsyah Widarni (Jurnal Riset Multidisiplin Edukasi, 2026)
Child grooming is a form of crime that targets children and adolescents through emotional manipulation for the purpose of exploitation. This legal awareness program aims to increase adolescents' understanding of the dangers of child grooming and ways to prevent it. The results showed an improvement in participants' awareness and vigilance regarding this issue.